Actual problems of the land market – analysis and solutions - Hroshko, Borys (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The introduction of the land market is one of the key and final stages of the land reform in Ukraine, which has been ongoing almost since independence. This reform is designed to introduce effective land use and positively affect the agricultural sector.Over the years, the issue of the introduction of the land market has been controversial and politicized, and has caused numerous disputes. However, both legal and economic negative effects of the moratorium on the sale of agricultural products grew and harmed the Ukrainian economy.The main tasks of the land market are: сreating a positive investment climate in the agricultural sector; іncreasing the competitiveness of the economy both domestically and in external markets; achieving a positive socio-economic effect for economic growth; legalizing and bringing the land market out of the «shadow».The fulfillment of these tasks is impossible without high-quality legal regulation. The article analyzes a number of legal problems related to the land market and offers options for their solution. It is noted that legal restrictions on access to the land market for legal entities and foreign investors do not allow to achieve positive economic effects in full. The problems that arise in the implementation of the preemptive right to purchase agricultural land plots are revealed and options for their solution are proposed. The need to change the approach to taxation of transactions with agricultural land is substantiated. The issue of pricing is revealed and the experience of the Czech Republic in this field is analyzed.